Concordance between transrectal ultrasound guided biopsy results and radical prostatectomy final pathology: Are we getting better at predicting final pathology? - Walker, Richard (Canadian Medical Association, 2014)
INTRODUCTION: Inaccuracy in biopsy Gleason scoring poses a risk to men who may then receive inappropriate treatment. We assess whether there was a change in discordance rates between biopsy and radical prostatectomy at our institution in recent years, while considering the implementation of active surveillance and the shift in biopsy scores caused by the 2005 International Society of Urologic Pathology update to the Gleason scoring protocol. METHODS: We reviewed patients who underwent radical prostatectomy at our institution between May 2004 and April 2011. We analyzed clinical and pathological correlates of upgrading in 3 subgroups: Gleason sum (GS) 6/6, GS6/7 and GS7/7, where the sum preceding the dash was determined from biopsy and the subsequent sum was determined from the radical prostatectomy specimen. We applied the log-rank test and Cox model to a Kaplan Meier analysis of biochemical recurrence in the subgroups, and also mapped GS6/7 discordance over time. RESULTS: In total, 1717 patients met our inclusion criteria. The 3 subgroups had significantly different mean prostate-specific antigen, patient age, tumour volume, margin status, pathologic stage, prostate weight, transrectal ultrasound volume and rate of progression (p < 0.05). We noted a multiphasic trend with a fall in discordance after 2005. However, there was no sustained trend over the study period taken as a whole (p = 0.06). CONCLUSIONS: Although no sustained trend was observed, the falling discordance after 2005 may reflect the accommodation to the Gleason scoring update, while the gradual adoption of active surveillance may have led to the otherwise increasing trends. However, our observations may also be spurious biopsy sampling errors.